Problem Based Learning with Collaborative Digital Reading Improves Interactive Conversation and Literacy: Problem Based Learning dengan Bacaan Digital Kolaboratif Meningkatkan Percakapan Interaktif dan Literasi - Istiqomatudiniyah; Viarti Eminita (Academia Open, 2026)
General Background: Interactive conversation skills and literacy are fundamental competencies in 21st-century elementary education, supporting communication, collaboration, and critical thinking. Specific Background: Fourth-grade students at SDN Tegal Kunir Lor II demonstrated low interactive conversation skills and literacy, associated with conventional instruction, minimal integration of digital technology, and limited collaborative learning practices. Knowledge Gap: Previous studies have examined Problem Based Learning (PBL), digital reading, or collaborative approaches independently, yet empirical evidence integrating these three components within a single experimental framework remains limited. Aims: This study analyzes the partial and simultaneous effects of PBL with collaborative digital reading on students’ interactive conversation skills and literacy. Results: Using a quasi-experimental pretest–posttest control group design involving 40 students, multivariate analysis indicated a significant difference between groups (Pillai’s Trace = 0.858; F = 111.728; p < 0.05). Partial analysis showed significant differences in interactive conversation skills (F = 173.709; p < 0.05; R² = 0.821) and literacy (F = 2.376; p < 0.05; R² = 0.059). Novelty: The study integrates PBL, collaborative digital reading, and simultaneous multivariate analysis of communication and literacy outcomes in primary education. Implications: The findings recommend PBL with collaborative digital reading as an alternative instructional model to develop interactive communication and literacy competencies in elementary classrooms. Highlights• Multivariate analysis confirmed significant differences across both assessed competencies.• Experimental group demonstrated higher posttest mean scores than the control group.• Problem-solving activities combined with group-based digital texts supported measurable learning outcomes. KeywordsProblem Based Learning; Collaborative Digital Reading; Interactive Conversation Skills; Literacy; Elementary Education